Matrix Gla Protein and Nitric Oxide Synthase-3 Genetic Variants in Chronic Kidney Disease and Their Relation with Cardiovascular Risk - G. Priyadarshini; Sreejith Parameswaran; Jayaprakash Sahoo; Sandhiya Selvarajan; Ananthakrishnan Ramesh; Medha Rajappa (International Journal of Nephrology)
Background. Chronic kidney disease (CKD) is defined by gradual deterioration of renal parenchyma and decline of functioning nephrons. The risk of cardiovascular events is drastically increased in patients with CKD. This complicated link of CKD and cardiovascular disease (CVD) is not well understood till date. Objective. We aim to study the influence of genetic variants of matrix Gla protein (MGP) gene rs1800801, rs1800802, and rs4236 and nitric oxide synthase-3 (NOS3) gene rs1799983 and rs2070744 on the risk of CKD and its associated cardiovascular comorbidity in South Indian Tamils. Methods. One hundred and eighty-five CKD patients and 185 controls were recruited in this research. Flow-mediated dilatation (FMD) of brachial artery was measured ultrasonically. Circulating levels of MGP and nitric oxide (NO) were measured by ELISA. Genotyping was done by real-time PCR. Results. We observed a significant difference in the distribution of TT and CT genotypes of NOS3 (rs2070744), indicating an increase in the risk of CKD. NO level was significantly decreased in CKD cases than controls. We also found a significant difference in the distribution of TTA and CCG haplotypes of MGP polymorphisms (1-rs4236; 2-rs1800801; 3-rs1800802) between the groups, indicating an increase in the risk of CKD. CT genotype of MGP (rs4236) and CT genotype of NOS3 (rs2070744) variants were found to be associated with decreased FMD, indicating endothelial dysfunction, the harbinger of CVD. Conclusion. We conclude that genetic variants of MGP and NOS3 enhance the risk of CKD and its associated cardiovascular comorbidity in South Indian Tamils.